2003
DOI: 10.4049/jimmunol.171.11.5940
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Charged with Apoptotic Tumor Cells Induce Long-Lived Protective CD4+ and CD8+ T Cell Immunity against B16 Melanoma

Abstract: Dendritic cells (DCs) are potent APCs and attractive vectors for cancer immunotherapy. Using the B16 melanoma, a poorly immunogenic experimental tumor that expresses low levels of MHC class I products, we investigated whether DCs loaded ex vivo with apoptotic tumor cells could elicit combined CD4+ and CD8+ T cell dependent, long term immunity following injection into mice. The bone marrow-derived DCs underwent maturation during overnight coculture with apoptotic melanoma cells. Following injection, DCs migrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 54 publications
4
152
2
Order By: Relevance
“…Meanwhile, it became clear that immune responses can be generated outside secondary lymphatic tissue [23,32] and that tumors are not simply ignored by the immune system even if they grow at extra-lymphatic sites [33]. Cross-presentation of tumor-associated antigens by DC rather than direct antigen presentation by tumor cells is operative in recognition of tumor cells by the immune system and induction of immunity or tolerance [34][35][36]. However, processing of tumor antigens critically depends on DC subtype and on the mode of antigen delivery [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it became clear that immune responses can be generated outside secondary lymphatic tissue [23,32] and that tumors are not simply ignored by the immune system even if they grow at extra-lymphatic sites [33]. Cross-presentation of tumor-associated antigens by DC rather than direct antigen presentation by tumor cells is operative in recognition of tumor cells by the immune system and induction of immunity or tolerance [34][35][36]. However, processing of tumor antigens critically depends on DC subtype and on the mode of antigen delivery [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Another important determinant of tumor-specific T cell responses is the functional state of the antigen-presenting DC. Activated, mature DC promote tumor immunity [34], whereas immature DC rather favor development of T cell tolerance towards tumor-associated antigens [39]. Moreover, uptake of apoptotic cell material itself leads to a hypo-reactive state of DC [40].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that apoptotic bodies were favorable for DC presenting tumor antigens. [48][49][50][51][52] Therefore, apoptosis of the CD154-tranfected cells after administration in vivo may even be favorable for immunotherapy. Human clinical studies are underway to determine the effectiveness of CD154-transfected B-CLL cells in producing in vivo immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…14 More recently, it has further been shown that DC charged with apoptotic tumor cells induced long-lived protective CD4 þ and CD8 þ T-cell immunity 15 and apoptotic, but not necrotic, tumor cells are efficient vaccines in vivo. 16 Apparently contradicting these results, it has also been reported that the presence of apoptotic cells during macrophage activation increases their secretion of anti-inflammatory mediators 17 and decreases their secretion of proinflammatory cytokines, 18 and that apoptotic cells are actually able to induce suppression of inflammatory responses and tolerance. 19,20 In line with this notion, there is evidence for the lack of immunogenicity 21 or reduced immunogenicity of apoptotic tumor cells as compared with viable counterparts.…”
Section: Introductionmentioning
confidence: 98%